Pseudopolymorphs – a variety of self-organization of para-sulphonato-calix[8]arene and phenanthroline in the solid state. Issue 46 (4th November 2016) - Leśniewska, Barbara; Coleman, Anthony W.; Tauran, Yannick; Perret, Florent; Suwińska, Kinga
Abstract : The paper presents results concerning construction of inclusion complexes of para -sulphonato-calix[8]arene with 1, 10-phenanthroline. Abstract : The paper presents results concerning construction of inclusion complexes of para -sulphonato-calix[8]arene with 1, 10-phenanthroline. Structures of crystalline host–guest complexes were determined by means of X-ray diffraction. Intermolecular interactions were analyzed and the organization of ions and molecules in the crystal lattice was described.